Cellular Changes during Fruit Ripening of Harumanis Mango - Muhammad, H.; Ding, Phebe (2006)
A study of cellular changes in the skin and pulp of Harumanis mango fruit during ripening was carried out. Mature green mango (day 0) was collected from Department of Agriculture, Perlis. Fruits were ripened in a fibre board cartoon at 270C using 20 g calcium carbide/kg fruit for 24 h. tissue of fruit at day 0, 2 and 4 were processed and viewed under scanning electron microscope. From this study, two region were identified in Harumanis mango fruit as ripening progressed, namely the skin and pulp regions. The skin was composed by a single layer of epidermis with well-defined cuticle. The cell containing crystals i.e. the idiodblast could be seen in the skin region of Harumanis mango fruit especially in ripening day 4. resin ducts could be seen in skin and pulp regions. The ducts exist as regions and ripening days. As ripening progressed, the cell loses its integrity and starch granules were degraded.